Seismic Hazard Identification in the North Banda Arc Region Using Gutenberg-Richter Law - Silvia Lestari; Sungkono (Jurnal Fisika dan Aplikasinya, 2025)
The North Banda Arc region has a high risk of significant earthquakes due to its complex tectonic configuration. In order to assess seismic hazard potential of the North Banda Arc region, Gutenberg-Richter (G-R) Law is applied using earthquake catalogue from 1970 to 2023. The results are G-R parameters, including Mc, a, and b, where the spatial parameters (a and b values) and temporal parameter (b-value) are applied to investigate the seismic hazard in the North Banda Arc Region. The spatial results show that two regions with high risk to strong earthquakes occur are on eastern Seram Island and between eastern Buru and western SeramIsland, including its smaller islands nearby. On the other side, temporal result shows a decreasing b-value, indicating an increasing effective stress that could lead to a strong earthquake.